Problems During the Throttle Body Production Process at PT HK Manufacturing - Alfajri, Aktsa; Fadlan, Khafi Dehan; Alfatih, Muhamad; Alwan, Naufal; Prasetyo, Teddy; Prastyo, Yudi (Lentera Ilmu Nusantara, 2025)
The throttle body is one of the important components in the vehicle's fuel system, especially those that use electronic fuel injection (EFI) technology. This component serves as the main conduit to deliver air to the intake manifold. However, in the production process of throttle bodies, there are a number of problems that affect product quality, such as leaks, dents, pin holes, yuhike, and rust. These problems not only impact the efficiency of vehicle use, but also reduce consumer satisfaction and increase production costs due to wasted time on repairs. This study aims to identify the main causes of these problems, such as errors in the installation of components, inappropriate temperature conditions, and the influence of humidity. With quantitative methods, this research involves observation and visual inspection on the products produced, including leak tests with Leak Test machines. The results of the study show the need for design improvement, material quality control, and the implementation of better production strategies to reduce the defect rate. The implementation of this solution is expected to increase production efficiency, optimize the quality of the throttle body, and meet consumer needs and desires.